2021
DOI: 10.1093/rheumatology/keab046
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for eosinophilic granulomatosis with polyangiitis: a systematic review of observational studies

Abstract: Objective to analyze the available evidence about the use of rituximab (RTX) and other biologic agents in Eosinophilic Granulomatosis with Polyangiitis (EGPA) patients and to provide useful findings to inform the design of future, reliable clinical trials. Methods A systematic review was performed. A systematic search was conducted in PubMed/MEDLINE, Scopus, Web of Science and the Cochrane library databases and an extensive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…In recent reviews, rituximab was found it may help induce and sustain remission in patients with newly diagnosed or relapsing EGPA especially for ANCA-positive patients [31,32]. But in the past, we did not find definite evidence for rituximab in CNS involvement of EGPA.…”
Section: Discussionmentioning
confidence: 78%
“…In recent reviews, rituximab was found it may help induce and sustain remission in patients with newly diagnosed or relapsing EGPA especially for ANCA-positive patients [31,32]. But in the past, we did not find definite evidence for rituximab in CNS involvement of EGPA.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, for active or relapse adult EGPA patients with severe disease, the 2021 ACR/Vasculitis Foundation Guideline has suggested RTX 375 mg/m 2 weekly × 4 or one gram on days 1 and 15 for remission induction, and 500 mg every 6 months or one gram every 4 months for remission maintenance [ 11 ]. In a recent systemic review in RTX-treated EGPA cases, negative-ANCA was found in 35%, while at least two organs were involved and/or neuropathy in 84% of cases [ 31 ]. Under the one gram fortnightly regimen given to 61% of patients, complete and partial remission were seen in 53% and 36%, respectively, with infection complications found in 19% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the 2021 ACR/Vasculitis Foundation Guideline has suggested to use RTX for the induction of active or relapse EGPA with severe activity, such as heart involvement [ 11 ]. Seroconversion after B-cell-depleting therapy might serve as a working mechanism in treating ANCA-positive EGPA with cardiac presentation [ 8 , 31 ], such as a seropositive endomyocarditis patient (case no. 4) under RTX therapy with multiple infusion courses.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, eosinophilic granulomatosis with polyangiitis (EGPA) patients were not included in these trials. However, multiple systematic reviews suggest that the drug can be helpful in inducing remission in such patients as well [ 166 , 167 ]. Regarding maintenance therapy, the MAINRITSAN trial of 115 patients demonstrated the advantage of a rituximab regimen (500 mg on days 0, 14, and months 6, 12, and 18) over azathioprine in preventing relapse up to a follow-up of 60 months [ 168 , 169 ].…”
Section: Rituximab In Dermatologic Conditionsmentioning
confidence: 99%